KORELASI ANTARAINFLASI DAN PENGANGGURAN - Ali Hardana (Institut Agama Islam Negeri Padngsidimpuan, 2015)
Inflation and unemployment are the two important variables tosee the economic condition in the country, inflation and unemploymenthave a negative relationship, when inflation rate has increases theunemployment rate will bed crease (phillip curve). Inflation rate alwaysincreasing every year and if the government can’t handle the inflationgrowth its possibly the economic crisis will happen again. This researchaims how the inflation rate influence the unemployment rate during 2002-2012. The analysis shows that there is at least the inflation andunemployment have the significant influence.